Основні цілі інформаційного реформування житлово-комунального господарства - Вантух, Ірина; Вовк, Наталія (Видавництво Львівської політехніки, 2012)
This article explores the usefulness of information for housing and utilities. The attention on the effectiveness of information habezpechennya and its impact on profitability of the utilities, which significantly affects their improvement in general.
Keywords: інформатизація; житлово-комунальне господарство України; інформаційне забезпечення; програма реформування